THE CONTENTS OF SCD40 AND INDICATORS OF DAMAGED ENDOTHELIUM IN PATIENTS WITH CHRONIC KIDNEY DISEASE - Topchii, I. I.; KirienkoА. N.; Dunaevskaya, M. M.; SchenyavskayaЕ. N.; Birukova, I. T. (Ukrainian Journal of Nephrology and Dialysis, 2017)
Introduction. Impairments of endothelial structure and functions of renal vessels are regarded as important factors of progression and chronization of chronic kidney disease (CKD). It is well known that the CD40/CD40L interaction is responsible for the aggregation of blood cells and their adhesion to the vascular wall, as well as its effect on the state of immune response. We investigated whether this interaction could be altered in patients with CKD and impaired immune status. Materials and methods. We examined 48 patients with chronic glomerulonephritis (CGN), 38 patients with chronic pyelonephritis and 42 patients with essential hypertension (EH) - control group. All patients received standard therapy with an ACE inhibitor perindopril in combination with a calcium channel antagonist amlodipine. Along with standard therapy the patients intravenously administered injections of "Kardioarginine." The degree of endothelial damage was assessed by the number of CEC and VE-cadherin content in blood plasma. In order to estimate changes in the immune status we determined the content of sCD40 in serum. Results. Increase in the content of serum sCD40 was shown for the CGN patients compared with healthy subjects and EH patients. The level of sCD40 in serum correlated with the number of CEC and VE-cadherin content in plasma. The use of kardioarginine combined with standard therapy led to reduction of sCD40 and stabilized the structure of endothelium. The loss of endothelial integrity in patients with CKD is apparently due to the activation of apoptosis with subsequent accelerated desquamation under the influence of activated white blood cells and the system of cytokines. Conclusions. The increase of sCD40 in patients with CKD may be a compensatory mechanism aimed to reduce the inflammatory activity by blocking the CD40/CD40L interaction at the cellular level.